2016
DOI: 10.1103/physrevb.94.245410
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of electronic structure of few-layer phosphorene from angle-resolved photoemission spectroscopy of black phosphorous

Abstract: A complete set of tight-binding parameters for the description of the quasiparticle dispersion relations of black phosphorous (BP) and N -layer phosphorene with N = 1 . . . ∞ is presented. The parameters, which describe valence and conduction bands, are fit to angle-resolved photoemission spectroscopy (ARPES) data of pristine and lithium doped BP. We show that zone-folding of the experimental three-dimensional electronic band structure of BP is a simple and intuitive method to obtain the layer-dependent two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…Prior to Cs deposition we recorded ARPES of the pristine BP crystal to confirm the surface quality and the orientation. We have obtained results in agreement with those published earlier [2,22]. Figures 1(c) and 1(d) show ARPES spectra (taken at hν = 21 eV with a horizontal entrance slit on the analyzer) after maximum deposition of Cs.…”
Section: Angle-resolved Photoemission Spectroscopysupporting
confidence: 90%
See 2 more Smart Citations
“…Prior to Cs deposition we recorded ARPES of the pristine BP crystal to confirm the surface quality and the orientation. We have obtained results in agreement with those published earlier [2,22]. Figures 1(c) and 1(d) show ARPES spectra (taken at hν = 21 eV with a horizontal entrance slit on the analyzer) after maximum deposition of Cs.…”
Section: Angle-resolved Photoemission Spectroscopysupporting
confidence: 90%
“…ARPES was performed at the BaDElPh beamline [23] of the Elettra synchrotron in Trieste, Italy, with linear s and p polarization at temperatures of 20 K. The crystal surfaces were prepared in situ in a vacuum better than 5 × 10 −11 mbar and at liquid-He temperatures by cleaving with a top post inside the analysis chamber [22]. Immediately after the cleave, we determined the high-symmetry directions through lowenergy electron diffraction.…”
Section: Angle-resolved Photoemission Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, angle resolved photoemission spectroscopy (ARPES) have so far been applied to get an information of hole bands (valence band) of bulk BP [25][26][27] as well as its band gap variation by alkali metal doping [28][29]. However, the electrons (holes) excited in the conduction (valence) band and their carrier dynamics have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the heterointerface (taking region 2 and 1, for example), calculations and transport measurement have showed that six-layer BP has a bandgap of ≈0.68 eV. [36,37] In comparison, a layer number of 11 will result in BP's bandgap below 0.4 eV, [34] www.advelectronicmat.de difference of BP sheets with similar thickness difference has also been revealed from electrical transport measurement. [35] This difference in a heterojunction is likely to give rise to an obvious current rectification behavior.…”
Section: Electrical Properties Of Bp Heterojunction Diodementioning
confidence: 99%